An Analysis of the Effectiveness of Quantitative Assessment in Improving Islamic Religious Education Learning Outcomes at SDN 03 Plosokandang - Alamsyah, Alwi (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
Assessment in Islamic Religious Education (PAI) has been hampered by the subjectivity of assessment and the lack of measurable data. The dominant qualitative approach is not able to answer the need for more objective measurements. Therefore, this paper examines the concept and implications of quantitative assessment in PAI to realize a more objective, measurable, and accountable assessment system, so as to improve the quality of learning and the achievement of religious education goals in Indonesia. This study uses a case study at SDN 03 Plosokandang to examine the application of quantitative assessment in PAI learning. Data was collected through observation, interviews, and documentation. Quantitative assessment approach Through multiple-choice, true-false, and fill-in tests, research at SDN 03 Plosokandang regarding quantitative assessment methods in Islamic Religious Education involves the collection of numerical data from various activities, including classroom test observation, student performance assessment, and portfolio collection. This data is analyzed quantitatively to understand assessment practices. Quantitative assessment in Islamic Religious Education has a number of benefits. For example, it can assist teachers in measuring students' abilities in more detail and objectively, as well as facilitating comparisons between students and providing clear feedback.